Solute carrier protein family: physiological functions, disease associations, and therapeutic potential in immune-related disorders - Li, Peiyan; Liu, Chen; Niu, Yewei; Wu, Peitao; Liu, Lixuan; Jin, Jiamin; Yang, Jinfeng (Frontiers in Immunology, 2025)
The Solute Carrier Protein Family (SLC) is responsible for the uptake and transport of a variety of substances across the cell membrane. It plays a central role in maintaining the stability of the intracellular environment through participation in metabolic processes and the transport of drugs and toxins. The highly tissue-specific expression of SLC proteins endows them with potential applications in disease treatment and drug development. Transplant immune reactions are a major challenge in the field of organ transplantation, as graft rejection is a key factor determining the success of transplantation and long-term organ survival. SLC proteins are increasingly drawing attention for their roles in modulating immune responses, influencing transplant immune tolerance, and controlling graft rejection. By regulating the metabolism and function of immune cells, SLC proteins affect the formation and tolerance of transplant immune responses. Among them, 7 SLC proteins are “validated targets” with approved or phase III drugs, 9 are “candidate targets” in active clinical trials, and 14 remain “potential targets” supported by genetic and pre-clinical evidence. This article elucidates the functions of SLC proteins in transplant immunology, inflammation and autoimmune diseases, tumor immunology, metabolic diseases, and neurological diseases, as well as the new targets and strategies for treating these diseases that SLC proteins provide.